INDUSTRIALISED BUILDING SYSTEM (IBS) IN PUBLIC BUILDING CONSTRUCTION: PROFITABILITY ON THE IMPLEMENTATION IN SCHOOL BUILDING - Shafikah Saharuddin; Nazirul Syazani Shamsudin; Noor Anisah Abdullah@Dolah; Mohd Khairul Amri Ramly; Nur Fatiha Mohamed Yusof; Siti Nur Aishah Mohd Noor (Journal of Islamic, Social, Economics and Development, 2022)
Industrialized Building System (IBS) was introduced and developed in Malaysia tobe part of the solution to address the increasing demand for affordable housing, providinganswer on foreign labour problems, improving cost effectiveness, and ultimately refining thequality, efficiency, and productivity of the construction industry. This paper intended to identifyand discover the profitability factors from IBS application among contractors. Quantitativemethod of questionnaires survey was distributed to various contractors in Selangor which haveexperienced IBS construction mainly on public building projects. Ideally, the researcher foundthat by reducing number of labour, enhancing the knowledge of IBS player, reducingconstruction period and reducing waste material on site area are among the factors that bringprofitability upon using IBS method.